Categorization of Road Accidents Related to the Default of Signaling: A Case Study of the Yaoundé-Douala Highway, Southern Cameroon - Armand, Zogo Tsala Simon; Merlin, Ayissi Zacharie; Anicet, Noah Pierre Marcel; Fabien, Betene Ebanda; Max, Ayina Ohandja Louis (New Approaches in Engineering Research Vol. 12, 2021)
This chapter highlights the typology of road accidents related to the default of signing for many accidents have occurred due to imperfect signposting along roads in Cameroon. The Yaoundé-Douala highway has been chosen for this study. Available Field data recorded during the years 2007, 2009 and 2011, have enabled the analysis of each accident. It appears that amongst the 569 accidents recorded along a section of 114 km, 108 cases (about 20%) result from the default or lack of signing. From a clinical analysis, four scenarios of accidents that occurred by collision were found on one hand, and on the other hand, seven were elaborated based on factors such as: no signposting at crossroads, the lack of vertical and/or horizontal alignment or slightly raised bump and the deficiency of signpost for normal parking layouts or no parking at certain critical points.